Microporous Brookite-Phase Titania Made by Replication of a Metal–Organic Framework. - Shoji Hall, Anthony; Atsushi Kondo; Kazuyuki Maeda; Mallouk, Thomas E. (Journal of the American Chemical Society, 2013)
Metal–organic frameworks (MOFs) provide access to structures with nanoscale pores, the size and connectivity of which can be controlled by combining the appropriate metals and linkers. To date, there have been no reports of using MOFs as templates to make porous, crystalline metal oxides. Microporous titania replicas were made from the MOF template HKUST-1 by dehydration, infiltration with titanium isopropoxide, and subsequent hydrothermal treatment at 200 °C. Etching of the MOF with 1 M aqueous HCl followed by 5% H2O2 yielded a titania replica that retained the morphology of the parent HKUST-1 crystals and contained partially ordered micropores as well as disordered mesopores. Interestingly, the synthesis of porous titania from the HKUST-1 template stabilized the formation of brookite, a rare titania polymorph.